Magnetic core and method for manufacturing the same
A silica film coating with 37,000 mm^-1 roughness on magnetic cores addresses adhesive penetration issues, enhancing reliability and yield by improving penetration resistance and enabling stable electrode formation.
Patent Information
- Application Number
- JP2021502187
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-02-25
- Filing Date
- 2020-02-21
- Publication Date
- 2025-02-04
- Estimated Expiration
- 2040-02-21
AI Technical Summary
Existing magnetic cores face issues with adhesive penetration due to porosity and shape complexity, leading to reliability concerns and reduced yield, despite sealing methods like glass layers and filling materials.
A silica-based film coating with an average arithmetic surface roughness of 37,000 mm^-1 is applied to the magnetic core surface, enhancing penetration resistance and allowing for stable electrode formation.
The silica coating improves magnetic core reliability and yield by preventing adhesive penetration, ensuring effective adhesive resistance and enabling stable electrode formation.
Smart Images

Figure 0007626063000002 
Figure 0007626063000003 
Figure 0007626063000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a magnetic core and a method for manufacturing the magnetic core. [Background technology]
[0002] Coil components such as inductors, transformers, and chokes have traditionally been used in a wide variety of applications, including home appliances, industrial equipment, and vehicles. Coil components are composed of a coil disposed around a magnetic core, and ferrite, which has excellent magnetic properties, freedom in shape, and cost, is widely used for such magnetic cores.
[0003] In recent years, power supply devices for electronic devices have become smaller, and they are now required to be usable in a wider variety of environments. As a result, there is a growing demand for coil components that are small and low-profile, and can be used in high-temperature environments exceeding 130°C, and with large currents. For such coil components, magnetic cores using metallic soft magnetic materials, which have a higher Curie temperature and a higher saturation magnetic flux density than ferrite, are increasingly being used. As metallic soft magnetic materials, magnetic particles such as Fe-Si, Fe-Ni, Fe-Si-Al, and Fe-Cr-Al alloys are used.
[0004] It is known that ferrite cores manufactured by sintering and dust cores using metallic soft magnetic materials are generally porous with fine gaps and pores. Patent Document 1 describes providing a glass layer on the surface of the core to prevent adhesive from seeping into the fine gaps in the ferrite core. Patent Document 2 describes filling the pores in a dust core using a metallic soft magnetic material with a permeation prevention material to prevent the permeation of adhesives, etc. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2011-014730 A [Patent Document 2] JP 2013-045926 A Summary of the Invention [Problem to be solved by the invention]
[0006] In Patent Documents 1 and 2, the penetration of adhesive is suppressed by sealing a porous magnetic core. However, the shape of the magnetic core is complex, and the amount of pores is likely to be biased due to density differences during molding, and the formation and filling conditions of the coating made of a material for preventing penetration, such as a glass layer, are also likely to vary. Therefore, there are cases where the effect of suppressing penetration is not sufficient. In the first place, it is not easy to determine whether a magnetic core after sealing has sufficient penetration suppression performance, and the only way to check the penetration state is to actually apply an adhesive or the like.
[0007] Therefore, an object of the present invention is to provide a magnetic core with excellent permeation suppression performance. [Means for solving the problem]
[0008] According to one embodiment of the present invention, a coating surface is provided at least partially coated with a siliceous coating, and the arithmetic mean curvature of peaks (Spc: ISO25178) of the coating surface is 37000 mm -1 The following magnetic core can be provided: According to this, a magnetic core with excellent permeation suppression performance can be provided.
[0009] In one embodiment of the present invention, the magnetic core preferably has a structure in which magnetic particles of an Fe-M (M is a metal that is more easily oxidized than Fe) based alloy are bonded together via oxides derived from the magnetic particles.
[0010] In one embodiment of the present invention, the siliceous coating preferably contains a siloxane bond (-Si-O-Si- bond).
[0011] In one embodiment of the present invention, the oxide contains the M, and it is preferable that the M contained in the oxide is at least one of Al and Cr.
[0012] In one embodiment of the present invention, it is preferable that the coating surface has an electrode formed thereon.
[0013] According to another embodiment of the present invention, at least a part of the magnetic core is coated with a siliceous coating, and the arithmetic mean curvature of the peaks (Spc: ISO25178) is 37000 mm -1 It is possible to provide a method for manufacturing a magnetic core, comprising the steps of forming a coating surface as described below, and forming an electrode on the coating surface. This allows the electrode to be formed on a coating surface with excellent permeation suppression performance, and is expected to improve the reliability and yield of the magnetic core.
[0014] In another embodiment of the present invention, the magnetic core preferably has a structure in which magnetic particles of an Fe-M (M is a metal that is more easily oxidized than Fe) based alloy are bonded together via oxides derived from the magnetic particles.
[0015] In another embodiment of the present invention, the siliceous coating preferably contains a siloxane bond (-Si-O-Si- bond).
[0016] In another embodiment of the present invention, the oxide contains the M, and it is preferable that the M contained in the oxide is at least one of Al and Cr.
[0017] In another embodiment of the present invention, the siliceous coating is preferably formed by carrying out a step of applying a siliceous coating forming treatment liquid to the surface of the magnetic core and curing the liquid at least once. Effect of the Invention
[0018] According to the present invention, it is possible to provide a magnetic core having excellent permeation prevention performance, which can contribute to improving the reliability and yield of the magnetic core. Also, according to the present invention, it is possible to form an electrode on a coating surface having excellent permeation prevention performance, which can contribute to improving the reliability and yield of the magnetic core. [Brief description of the drawings]
[0019] [Figure 1]1 is a graph for explaining the relationship between the arithmetic mean curve of peaks (Spc: ISO25178) of a surface coated with a siliceous film and the permeation prevention performance. [Diagram 2] This is an enlarged SEM image of the surface of a magnetic core that is not covered with a siliceous coating. [Diagram 3] This is an SEM image showing an enlarged view of the coating surface of a magnetic core coated with a siliceous film. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] Hereinafter, the embodiments of the present invention will be described in detail, but the present invention is not limited thereto.
[0021] The magnetic core of this embodiment is a porous core made of ceramic-based soft magnetic material such as Ni-based ferrite or magnetic particles of the above-mentioned metal-based soft magnetic material, and at least a part of the surface is coated with a silica coating. -1 By satisfying the following, the surface of the coated surface can be made to have a gentle shape, and accordingly, a magnetic core with improved permeation prevention performance can be obtained, in which the permeation of adhesives and the like applied to the coated surface is suppressed. The arithmetic mean curve of peaks (Spc: ISO25178), which three-dimensionally evaluates the surface properties of the coated surface, is specified in ISO25178 of the International Organization for Standardization, and can be easily measured using measuring instruments such as a laser microscope, which will be described later.
[0022] ISO25178 also includes other parameters of three-dimensional surface roughness such as arithmetic mean height Sa, maximum height Sz, aspect ratio Str, and developed area ratio Sdr. Of these, it has been discovered that for magnetic cores having a coated surface, at least a portion of which is covered with a siliceous film, by giving the coated surface a unique surface profile defined by the arithmetic mean curve Spc of the peaks, it is possible to provide a magnetic core with excellent permeation prevention performance.
[0023] The magnetic core of this embodiment may be porous with a porosity of 5 to 25%. The metallic soft magnetic material is preferably magnetic particles of a soft magnetic alloy containing Fe and an element M that is more easily oxidized than Fe. As a first aspect of the soft magnetic material of the magnetic core, the soft magnetic alloy is preferably a soft magnetic alloy containing 3% by mass or more and 16.0% by mass or less of Al, 3% by mass or more and 7.0% by mass or less of Cr, with the balance being Fe and unavoidable impurities, where the sum of Fe and M (Al and Cr) is 100% by mass.
[0024] In addition, a second embodiment of the soft magnetic material for the magnetic core is preferably a soft magnetic alloy containing 1.5% by mass or more and 8% by mass or less of M, more than 1% by mass or more and 7% by mass or less of Si, with the sum of Fe, M (Al or Cr), and Si being 100% by mass, and the remainder being Fe and unavoidable impurities.
[0025] In the first and second embodiments described above, C, Mn, P, S, O, Ni, N, etc. may be contained as inevitable impurities. The contents of these inevitable impurities are preferably C≦0.05 mass%, Mn≦1 mass%, P≦0.02 mass%, S≦0.02 mass%, O≦0.5 mass%, Ni≦0.5 mass%, and N≦0.1 mass%, respectively. In the first embodiment, Si may also be contained as an inevitable impurity in an amount of 0.5 mass% or less.
[0026] The shape of the magnetic particles of the soft magnetic alloy is not particularly limited, but for example, from the viewpoint of fluidity, etc., it is preferable to use magnetic particles produced by an atomization method, which makes it easier to obtain relatively spherical particles from a molten metal adjusted to a predetermined composition. Atomization methods such as gas atomization and water atomization are suitable for producing magnetic particles of alloys that are highly malleable and ductile and difficult to crush.
[0027] The average particle size of the magnetic particles (here, the median diameter D50 in the cumulative particle size distribution is used) is not limited to this, but for example, those having an average particle size of 1 μm or more and 100 μm or less can be used. When the magnetic particles are filled into a molding die, if particles with large particle sizes are adjacent to each other, large gaps are formed between the particles, and the filling rate does not increase, and the density of the molded body obtained by pressure molding tends not to increase. For this reason, it is preferable to classify the magnetic particles and remove particles with large particle sizes. As a classification method, dry classification such as sieving classification can be used, and it is preferable to obtain magnetic particles at least under 32 μm (i.e., passed through a sieve with an opening of 32 μm). By reducing the average particle size, the strength, core loss, and high-frequency characteristics of the magnetic core are improved, so the average particle size (median diameter D50) is more preferably 15 μm or less. On the other hand, if the average particle size is small, the magnetic permeability decreases, so the average particle size (median diameter D50) is more preferably 5 μm or more.
[0028] It is preferable to mix the magnetic particles with a binder and form them into granules by granulation. This improves the fluidity and filling properties in a die when forming the magnetic core, and also allows the magnetic particles to be bonded together during pressure forming, giving the molded body strength that can withstand handling after forming. There is no particular limit to the type of binder, but for example, organic binders such as polyethylene, polyvinyl alcohol, and acrylic resins can be used. It is also possible to use inorganic binders that remain after heat treatment.
[0029] The amount of binder added should be sufficient so that the binder is distributed sufficiently between the magnetic particles and the strength of the molded body is sufficiently ensured, but if the amount of binder added is too large, the density and strength of the molded body tend to decrease. From this viewpoint, the amount of binder added is preferably 0.2 to 10 parts by weight, and more preferably 0.5 to 3.0 parts by weight, per 100 parts by weight of the magnetic particles.
[0030] The method of mixing the magnetic particles and the binder is not particularly limited, and any conventionally known mixing method or mixer can be used. As the granulation method, for example, a wet granulation method such as rolling granulation or spray drying granulation can be used. Among them, spray drying granulation using a spray dryer is preferable, as the shape of the granules approaches spheres, and the time of exposure to heated air is short, making it possible to obtain a large amount of granules.
[0031] The resulting granules have a bulk density of 1.5 to 2.5 × 10 3 kg / m 3 and an average particle size (D50): preferably 60 to 150 μm. Such granules have excellent flowability during molding, and the gaps between the magnetic particles are small, improving the filling ability into the mold, resulting in a compact with a high density and a magnetic core with high magnetic permeability. In order to obtain a desired granule size, classification using a vibrating sieve or the like can be used.
[0032] In order to reduce friction between the granules and the molding die during pressure molding, it is preferable to add a lubricant such as stearic acid or a stearate salt. The amount of lubricant added is preferably 0.1 to 2.0 parts by weight per 100 parts by weight of the magnetic particles. The lubricant can also be applied to the die.
[0033] The magnetic particle granules are subjected to pressure molding. In pressure molding, a press machine such as a hydraulic press or servo press and a molding die are used to mold the mixed powder into a predetermined shape such as a toroidal shape or a rectangular parallelepiped shape. This pressure molding may be room temperature molding, or, depending on the binder material, may be warm molding in which the granules are heated to near the glass transition temperature at which the binder softens, but only to the extent that the binder does not disappear. The magnetic particles in the compact obtained by pressure molding are in point or surface contact with each other, and are adjacent to each other partially via gaps. The density of the compact is 5.6×10 3 kg / m 3 The above is preferred.
[0034] Annealing is performed at a temperature of 650°C to 900°C as a heat treatment for the compact. Annealing is performed in an oxygen-containing atmosphere, such as in air, a mixed gas of oxygen and an inert gas, or an atmosphere containing water vapor, among which heat treatment in air is simple and preferable. The oxide is obtained by the reaction between the magnetic particles and oxygen during heat treatment, and is produced by an oxidation reaction that exceeds the natural oxidation of the magnetic particles. The production of such oxides results in a high-strength magnetic core that has excellent insulation and corrosion resistance and is firmly bonded as grain boundaries between a large number of magnetic particles. In addition, the stress distortion introduced by pressure molding is alleviated, resulting in good magnetic properties.
[0035] The M elements Al and Cr that make up the soft magnetic alloy have a greater affinity with O (oxygen) than Fe and other non-ferrous metals. Therefore, during heat treatment, O in the air and O contained in the binder preferentially bind to Al and Cr near the surface of the magnetic particles, and are formed on the surface of the magnetic particles as chemically stable Al oxides, Cr oxides, or composite oxides with other non-ferrous metals. The formation of oxides containing M elements on the surfaces of the magnetic particles improves corrosion resistance and improves the insulation of the magnetic particles, reducing eddy current loss and improving the resistivity of the magnetic core. Since Al has a greater affinity with O than Cr, when Al and Cr are included as M elements, the degree of oxide formed tends to be dominated by Al oxides and suppressed by Cr oxides. The surface of the magnetic core is then covered with oxides of the magnetic particles.
[0036] In the magnetic core obtained through the heat treatment, the space factor (relative density) is preferably within the range of 75 to 95%. The porosity of such a magnetic core is 5% to 25%. The space factor (relative density) is calculated by calculating the density of the magnetic core from its dimensions and mass, and dividing the density of the obtained magnetic core by the true density of the magnetic particles. The true density of the magnetic particles can be determined by the density of an ingot produced by melting the same composition.
[0037] Next, a siliceous coating is formed on the surface of the obtained magnetic core. The siliceous coating has a molecular structure having a main chain in which three O and Si are siloxane-bonded (-Si-O-Si-). The siliceous coating may have a bond represented by (-Si-O-Si-), and may have a bond represented by (-Si-O-) repeated and continuous. A low-temperature method using a sol-gel method in which a sol of an alkoxysilane oligomer is gelled by hydrolysis through a condensation reaction is preferable as a method for forming such a siliceous coating on the surface of the magnetic core. The siliceous coating is preferably formed by immersing the magnetic core in a siliceous coating forming treatment liquid containing an alkoxysilane oligomer solution and colloidal silica, or by spraying the siliceous coating forming treatment liquid on the magnetic core and then subjecting it to a hardening treatment. The solvent of the siliceous coating forming treatment liquid is preferably a hydrophilic organic solvent such as an alcohol-based solvent or a glycol ether-based solvent. The siliceous coating itself has excellent heat resistance and high strength, and can improve corrosion resistance by covering the entire surface of the magnetic core.
[0038] As mentioned above, the surface of the magnetic core is covered with an oxide film due to the oxides of the magnetic particles, and in this film there are states in which metal elements originating from the magnetic particles are bonded with O, and in which metal elements are bonded with hydroxyl groups (OH). The hydroxyl groups or oxides on the surface of the magnetic core are chemically bonded, such as by covalent bonds or ionic bonds, with the hydroxyl groups in the siliceous film, increasing the adhesive strength between the magnetic particles and the siliceous film, thereby enabling the magnetic core and the siliceous film to adhere closely to each other.
[0039] A siliceous film is also formed on the voids inside the magnetic core that have been reached by the siliceous film-forming treatment liquid through the gaps between the magnetic particles on the surface of the magnetic core. The voids inside the magnetic core are filled with the siliceous film, and the formation of the siliceous film on the magnetic core surface (coated surface) gives the surface of the magnetic core a gentle shape. In other words, the pore-sealing state of the magnetic core can be easily confirmed by quantifying the state of the coated surface using the arithmetic mean curve of the peaks (Spc: ISO25178). When the arithmetic mean curve of the peaks (Spc: ISO25178) on the coated surface is 37,000 mm -1If the amount is less than the above, a magnetic core with excellent permeation suppression performance can be obtained. Note that by carrying out a process such as a vacuum impregnation method in which the magnetic core is immersed in the treatment liquid for forming a siliceous coating film and then degassed while being immersed in the treatment liquid for forming a siliceous coating film, and then releasing the vacuum state, the magnetic core can be impregnated with the treatment liquid for forming a siliceous coating film in one layer.
[0040] The method of applying the siliceous film forming treatment liquid to the magnetic core may be performed according to a known method such as a dip spin coating method, a dip coating method, or a spray coating method, and is not particularly limited. Depending on the viscosity of the siliceous film forming treatment liquid, the temperature may be adjusted to 100 to 200°C before application. The curing treatment may be performed, for example, at room temperature, but curing may be accelerated by placing the liquid at a temperature of about 40 to 200°C. The thickness of the siliceous film formed on the surface of the magnetic core is preferably about 0.5 to 10 μm. The thickness of the siliceous film can be adjusted by repeatedly applying the siliceous film forming treatment liquid to the surface of the magnetic core and curing it. As the film thickness increases, residual stress in the film makes it easier for cracks to occur on the surface side of the film. Although the occurrence of cracks can be suppressed by slowing down the curing speed, the film thickness is preferably 5 μm or less, more preferably 3 μm or less, in consideration of productivity.
[0041] An electrode can be formed on the coating layer of the magnetic core to form a magnetic core equipped with electrodes. -1 The coating layer described below has excellent permeation suppression performance and can stably form an electrode. As the electrode material, conductive materials such as Ag, Cu, Al, etc. (including alloys thereof) can be used. In addition, as a method for forming the electrode, for example, a method for adhesively fixing a metal terminal such as SPCC, copper alloy, Ni alloy, stainless steel, etc., a sputtering method, an ion plating method, or a printing method, a transfer method, a dipping method, etc. using a conductive paste may be used to form the electrode in a film shape. EXAMPLES
[0042] As magnetic particles, FeAlCr atomized powder (average particle size D50 ≒ 10 μm) containing 5 mass% Al, 4 mass% Cr, and the remainder Fe was prepared. A PVA (Poval PVA-205 manufactured by Kuraray Co., Ltd.) aqueous solution was used as a binder, and ion-exchanged water was used as a solvent. They were put into a stirring device and stirred and mixed to form a slurry. The blending ratio of the binder and ion-exchanged water was adjusted so that the PVA solid content was 0.75 parts by weight and the slurry concentration was 80 wt% for 100 parts by weight of the atomized powder. The slurry was spray-dried with a spray dryer. The slurry was sprayed inside the spray dryer and instantly dried with hot air at 240°C, and the granules that had become granular were collected from the bottom of the device. In order to remove coarse particles from the obtained granules, they were passed through a 100-mesh sieve, and the average particle size of the granules after passing through the sieve was within the range of 60 μm to 80 μm. Zinc stearate was added to the granules obtained by each of the above granulation methods in a ratio of 0.4 parts by weight per 100 parts by weight of the granules, and mixed in a mixer to obtain granules for molding.
[0043] The granules obtained above were filled into a mold and compressed to 5.8 g / cm using a hydraulic press. 3 , 6.3g / cm 3 The compact was formed at room temperature so as to obtain a compact density of 1. The shape of the compact was cylindrical with an outer diameter of 7.2 mm and a thickness of 2 mm.
[0044] The obtained compacts were subjected to a heat treatment in air at 750° C. for 1 hour to obtain the magnetic cores of Sample A and Sample B. The density was calculated from the dimensions and weight of the magnetic cores.
[0045] Next, the cylindrical magnetic core was placed in a stainless steel mesh cage and immersed in the treatment liquid for forming a siliceous film for 1 minute. The liquid temperature was 23°C. The treatment liquid for forming a siliceous film was a sealant from the Protector S series manufactured by Okuno Chemical Industries Co., Ltd. During immersion, the cage was swung to remove air bubbles attached to the magnetic core surface. The magnetic core was then placed in a centrifugal dehydrator, and the excess sealant attached at a peripheral speed of 8.4 m / s was removed, and the core was dried and hardened with hot air at 70°C. The coating process from immersion to drying was repeated 1 to 3 times. The condensation reaction also progresses in the hot air drying at 70°C, forming a siliceous film, but since unreacted portions remain, after the coating process, a hardening process was carried out again under the conditions of 120°C x 20 minutes, and the entire surface of the magnetic core was covered with a siliceous film.
[0046] The surface roughness of the obtained magnetic core was measured. The surface roughness was measured using a laser microscope VK-X120 manufactured by Keyence Corporation. The magnification was 100 times, the evaluation area was 145 μm × 109 μm, the cross-sectional curve was leveled (tilt adjustment) and smoothed, and the average arithmetic mean curve (Spc: ISO25178) of the peaks in five evaluation areas with different fields of view was obtained. The arithmetic mean curve (Spc: ISO25178) of the peaks was also obtained in the same manner for a magnetic core on which a siliceous coating was not formed. Figure 2 is an SEM image of the surface of sample A that was not coated at 1000 times, and Figure 3 is an SEM image of the surface of sample A that was coated twice at 1000 times.
[0047] An ink absorption test was used to confirm the pore sealing ability of the magnetic core. The test ink used was a surface energy evaluation pen (range 38 mN / m) manufactured by arcotest. The test ink was applied to the surface of the magnetic core, and the process was recorded as a video. In a still image taken 2 seconds after application, the test ink and other areas were binarized by computer, and the pore sealing ability was judged from the proportion of ink absorbed on the observation surface. If the ink absorption was less than 30%, it was judged as good, and if it was more than 30%, it was judged as bad.
[0048] The measurement results of the arithmetic mean curve of the peaks (Spc: ISO25178) for the coating surface of the siliceous film of the magnetic core and the results of the ink absorption test are summarized in Table 1 and Figure 1. In the table, a good result in the ink absorption test is indicated by ○, and a bad result is indicated by ×.
[0049] [Table 1]
[0050] As shown in Fig. 1, the arithmetic mean curve (Spc: ISO25178) of the peaks on the surface of the magnetic core covered with a silica-based film is 37,000 mm -1 If it is less than 37000mm, the ink absorption test will be judged as good. -1 If the thickness is over 37,000 mm, the result is a negative judgment, and it is clear that the permeation prevention performance of the magnetic core can be easily evaluated. Therefore, if the arithmetic mean curve (Spc: ISO25178) of the peaks of the coating surface covered with a siliceous coating is 37,000 mm, the result is a negative judgment. -1 By using the magnetic core described below, it is possible to obtain a magnetic core with excellent permeation suppression performance.
Claims
1. A coating surface is provided on at least a portion of the surface thereof, the coating surface being coated with a siliceous coating. The arithmetic mean curve (Spc: ISO25178) of the peaks on the coated surface is 37000 mm -1 is as follows: The soft magnetic alloy has a structure in which magnetic particles of the soft magnetic alloy containing Fe and an element M which is more easily oxidized than Fe are bonded to each other via an oxide derived from the magnetic particles, A magnetic core comprising voids between said magnetic particles, said voids being open to said surface and filled with said siliceous coating.
2. 2. The magnetic core according to claim 1, wherein the siliceous coating contains siloxane bonds (-Si-O-Si- bonds).
3. 3. The magnetic core according to claim 1, wherein the oxide contains M, and the M contained in the oxide is at least one of Al and Cr.
4. 4. The magnetic core according to claim 1, wherein the siliceous coating covers the entire surface of the magnetic core.
5. 5. The magnetic core according to claim 1, wherein the siliceous coating has a thickness of 10 μm or less.
6. 6. The magnetic core according to claim 1, further comprising an electrode formed on the coating surface.
7. At least a part of the magnetic core is coated with a siliceous film, and the arithmetic mean curve of the peaks (Spc: ISO25178) is 37000 mm -1 forming a coating surface, forming an electrode on the coated surface; the magnetic core has a structure in which magnetic particles of a soft magnetic alloy containing Fe and an element M that is more easily oxidized than Fe are bonded together via an oxide derived from the magnetic particles, A method for manufacturing a magnetic core comprising the steps of: forming a magnetic core having voids between the magnetic particles, the voids opening to the surface of the magnetic core and filled with the siliceous coating;
8. The method for producing a magnetic core according to claim 7, wherein the siliceous coating contains siloxane bonds (-Si-O-Si- bonds).
9. The method for producing a magnetic core according to claim 7 or 8, wherein the oxide contains M, and the M contained in the oxide is at least one of Al and Cr.
10. The method for producing a magnetic core according to any one of claims 7 to 9, wherein the siliceous coating covers the entire surface of the magnetic core.
11. The method for manufacturing a magnetic core according to any one of claims 7 to 10, wherein the thickness of the siliceous coating is 10 µm or less.
12. The method for producing a magnetic core according to any one of claims 7 to 11, wherein the siliceous coating is formed by carrying out a step of applying a siliceous coating forming treatment liquid to the surface of the magnetic core and curing the liquid at least once.
Citation Information
Patent Citations
Coil component
JP2011014730A
Electrode formation method of electronic component
JP2013045926A
Rare earth magnet and manufacturing method of the same
JP2016139705A
Manufacturing method of powder magnetic core
JP2018198319A
Powder magnetic core, and electromagnetic component
WO2019031209A1